The Role of Ethical Leadership in Building Organizational Trust and Commitment - Achmad Gani; Serlin Serang; Putri Aulia Radwa; Zulfikar (Jurnal Ilmu Manajemen Profitability, 2026)
Ethical leadership is increasingly important in organizational behavior because leaders’ ethical conduct can shape employees’ trust and commitment, yet the mechanism linking ethical leadership to organizational commitment requires further empirical examination. This study aimed to examine the effect of ethical leadership on organizational trust and organizational commitment and to determine the mediating role of organizational trust in this relationship. A quantitative explanatory design was employed, involving 250 employees from public, private, and manufacturing organizations. Data were collected through a structured and validated questionnaire and analyzed using Structural Equation Modeling to examine the relationships among ethical leadership, organizational trust, and organizational commitment. The results showed that ethical leadership had a positive and significant effect on organizational trust, indicating that leaders who demonstrated integrity, fairness, and moral responsibility were more likely to gain employees’ trust. Organizational trust also had a significant positive effect on organizational commitment, while ethical leadership directly and positively influenced organizational commitment. Furthermore, organizational trust partially mediated the relationship between ethical leadership and organizational commitment. These findings indicate that ethical leadership strengthens employee commitment both directly and through the development of organizational trust. The study contributes to organizational behavior research by clarifying the role of trust as an important mechanism through which ethical leadership influences employee commitment. Practically, the findings highlight the importance of ethical leadership development in strengthening trust, fostering long-term employee commitment, and supporting sustainable organizational performance.